Primary Ewing sarcoma of the kidney: a symptomatic presentation and review of the literature. (June 2013) - Hakky, Tariq S.; Gonzalvo, Americo A.; Lockhart, Jorge L.; Rodriguez, Alejandro R.
The objective of this review is to discuss the unique nature of primary renal Ewing sarcoma, including incidence, presentation and management. We also report on a common pattern of presentation, consisting of acute flank pain mimicking a renal stone colic, with or without hydronephrosis, and a renal mass discovered during imaging studies of renal Ewing sarcoma. We present our case of renal Ewing sarcoma along with imaging and pathological analysis. We also performed a retrospective review of all cases of renal Ewing sarcoma using PubMed. A total of 48 cases of renal EWS sarcoma have been reported and analyzed in this review. A mean age of 30.4 years was found along with a 61% male predominance. The mean survival was 26.14 months with a lower median survival in patients with advanced metastatic disease. Primary Ewing sarcoma of the kidney is rare. The diagnosis of primary renal EWS can be difficult and is based on a combination of electron microscopy, immunohistochemistry, chromosomal analysis, fluorescence in situ hybridization (FISH) and light microscopy.